ANALISIS KEMANDIRIAN EMOSIONAL PADA PESERTA DIDIK KELAS VIII MADRASAH TSANAWIYAH NEGERI 2 PONTIANAK - Emi Idayanti; Yuline Yuline; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
ABSTRACTEmotional autonomy is adolescents' ability to free themselves by de-idealizing their parents, self-reliance, and responsibility. These aspects involved: emotional autonomy of self-duty, biological basis, and psychological basis. Therefore, the researcher would like to find out deeper regarding the emotional autonomy of class VIII students in Madrasah Tsanawiyah Negeri 2 Pontianak. This research's problem is," How does the emotional autonomy of class VIII students' of Madrasah Tsanawiyah Negeri 2 Pontianak? Meanwhile, the purpose is to determine the emotional autonomy of class VIII students in Madrasah Tsanawiyah Negeri 2 Pontianak. Furthermore, the method used in this research was descriptive with the descriptive-survey study. The sample of this research was 37 students of class VIII of Madrasah Tsanawiyah Negeri 2 Pontianak. This research used a quantitative approach. The technique used to gather the data of this research was through indirect communication technique using a questionnaire. The data were analyzed using percentage calculation. The data analysis shows that the emotional autonomy from the self- duty of class VIII students of Madrasah Tsanawiyah Negeri 2 Pontianak reaches 75,93% categorized as "Moderate" afterward based on biological basis achieve 74,41% classified as "Moderate". Moreover, based on a psychological basis, reach up to 76,51% categorized as "Good".Keywords: Self- duty, Biological Basis, Psychological Basis.